2020
DOI: 10.1111/dth.14673
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of guselkumab in psoriasis patients who failed ustekinumab and/or anti‐ interleukin ‐17 treatment: A real‐life 52‐week retrospective study

Abstract: Recent major research advancements have significantly expanded our understanding of psoriasis pathophysiology, resulting in the development of highly effective, targeted therapies. Guselkumab is the first interleukin (IL)‐23 inhibitor approved for the treatment of moderate‐to‐severe‐psoriasis, providing a new therapeutical option for psoriasis. The aim of our study was to evaluate the efficacy of guselkumab in psoriatic patients who previously failed anti‐IL‐12/23 and/or anti‐IL‐17 treatment. A 52‐week single‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
67
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 21 publications
9
67
0
1
Order By: Relevance
“…Moreover, the population was limited to a small-scale and the Western population. 15 18 The patients previously treated with biologics in this study were less likely to achieve PASI 75 than biologic-naïve patients. Furthermore, lower PASI 75 response rate to guselkumab was noted as the number of previous biologics used increased.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Moreover, the population was limited to a small-scale and the Western population. 15 18 The patients previously treated with biologics in this study were less likely to achieve PASI 75 than biologic-naïve patients. Furthermore, lower PASI 75 response rate to guselkumab was noted as the number of previous biologics used increased.…”
Section: Discussionmentioning
confidence: 81%
“…These studies are mostly short-term, have small population sizes, and comprise non-Asian populations. 8 , 15 – 19 , 21 PASI 75 and PASI 90 responses to guselkumab in two short-term (16 weeks) multicentre real-life studies showed that 82.1% and 72.2% of patients achieved PASI 75, whereas 55.4% and 50.6% achieved PASI 90 at week 16. 8 , 15 Our patients responded to guselkumab even worse compared with those in other real-life studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations